Risk of serious infection with JAK inhibitors in immune-mediated inflammatory skin diseases: a meta-analysis of randomized clinical trials - Xinhong Su; Yushan Ou; Shifan Ruan; Xiaoqing Lv; Kun Qin; Jing Mao; Chao Ji (Journal of Dermatological Treatment)
Background Emerging research suggests that Janus kinase-signal transducer and activator of transcription (JAK-STAT) inhibitors may be associated with a higher risk of serious infection for patients with rheumatoid arthritis. However, there is no consensus on whether JAK inhibitors increase the risk of serious infection in patients with Immune-mediated inflammatory skin diseases (IMISDs).Objectives To ascertain the correlation between JAK inhibitor use and the risk of serious infection in patients with IMISDs.Methods PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), and registered Clinical Trials were searched up to June 1, 2024, using specific search terms related to JAK inhibitors and IMISDs. Randomized clinical trials (RCTs) comparing JAK inhibitors with a control group in patients with IMISDs were included. Studies focusing on cohort studies, case reports, case series, review articles, pooled analysis studies, post hoc analyses and topical JAK inhibitors were excluded. Data were extracted independently by two authors, focusing on serious infections defined according to each study’s criteria. Crude numbers for serious infections were pooled and underwent meta-analysis. We assessed the primary outcome regarding the occurrence of severe infections for each study.Results Thirty-two randomized clinical trials involving 11,917 patients were included. Serious infections were reported in 0.62% of patients receiving JAK inhibitors and 0.51% of controls. Meta-analysis found no significant increase in risk of serious infection (I2=0.00%, RR, 0.68; 95% CI, 0.43–1.07). Subgroup analyses revealed no significant heterogeneity based on condition (p = .56) or medication (p = .69).Conclusions This meta-analysis demonstrates that JAK inhibitors do not significantly increase the risk of serious infections in IMISD patients compared to control treatments. These findings support the safety of JAK inhibitors in this population. Future research should focus on real-world evidence to further assess their risk-benefit profile in dermatological practice.